Treatment Optimization of Electrocoagulation (EC) in Purifying Palm Oil Mill Effluents (POMEs) - R. Rusdianasari; Ahmad Taqwa; Jaksen Jaksen; Adi Syakdani (Journal of Engineering and Technological Sciences, 2017)
Palm oil mill effluents (POMEs) can contaminate soil, groundwater, and also the water environment. The increasing production of crude palm oil in Indonesia produces an enormous amount of POME waste. Therefore, a method is needed that can be used to purify POMEs. In this paper, an electrocoagulation (EC) method for purification of wastewater and a design to optimize this method are presented. An optimization experiment was performed by varying voltage and process time. The applied voltages were 6, 9, and 12 V and the process time was varied between 30 and 150 minutes. The measured parameters were: COD, BOD5, pH, TSS, lipids, and NH3-N. The result shows that optimum conditions were achieved at a voltage of 12 V and a process time of 150 minutes with COD at 8000 mg/L, BOD5 at 12000 mg/L, pH at 7.46, TSS at 324 mg/L, lipids at 17.8 mg/L, and NH3-N at 0.65 mg/L. The results are in accordance with environmental quality standards for pure water. This study proves that the proposed EC method is effective in purifying POMEs from pollutants.